Antibacterial non-woven fabric based on waste battery diaphragm and preparation method of antibacterial non-woven fabric
By recycling and processing waste lithium-ion battery separators, antibacterial non-woven fabrics are prepared, which solves the problems of unutilized separators and environmental pollution in the prior art, and realizes efficient recycling and environmentally friendly utilization of separators.
Patent Information
- Application Number
- CN202411904408.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
In the existing waste lithium-ion battery recycling and treatment process, the membrane is regarded as "waste". The resources cannot be fully utilized through combustion treatment, and smoke and harmful gases are generated, polluting the environment.
The waste battery is discharged, dehydrated, dried and disassembled, and the separator is screened and processed through hot water soaking of anionic surfactant, soaking organic solvents, rubbing and cleaning in water, and other steps, an antibacterial non-woven fabric is prepared. The preparation method of the nonwoven fabric includes meltblowing the precursor liquid and an antibacterial agent, or meltblowing it into a nonwoven fabric before impregnating the antibacterial agent.
The recycling rate of the diaphragm and the recycling value of ceramic materials are improved, the pollution to the environment is reduced, and the recycling value of waste diaphragm materials is improved through the preparation of antibacterial non-woven fabrics.
Smart Images

Figure CN119708617A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of waste battery treatment, and specifically relates to an antibacterial non-woven fabric based on waste battery diaphragms and a preparation method thereof. Background Art
[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] Lithium-ion batteries are currently commonly used energy storage devices for digital devices, new energy vehicles, etc. Lithium-ion batteries are mainly composed of four main parts: positive electrode materials, negative electrode materials, diaphragms, and electrolytes. Among them, the diaphragm material is one of the main components of lithium-ion batteries, which plays an important role in isolating the contact between positive and negative electrode materials and avoiding internal short circuits. With the use of lithium-ion batteries such as 3C digital products, power batteries, and energy storage batteries, the number of lithium-ion batteries has increased year by year, and it has also brought pressure on the disposal of waste power batteries. If waste batteries are not handled properly, the toxic and harmful substances in them will cause serious pollution to the air, soil, water sources and other environments.
[0004] As lithium batteries are retired and scrapped, they need to be disassembled and recycled, which will generate a large amount of waste diaphragms. As one of the four main materials of lithium-ion batteries, the diaphragm is mainly composed of a base film and a functional coating. In existing usage scenarios, only the base film or the base film plus the coating layer will be used according to demand. The base film is generally high-quality polypropylene or polyethylene, and the functional coating is polyvinylidene fluoride and ceramic coating. During the recycling and disassembly process, the diaphragm can be collected and utilized in various forms.
[0005] In the existing waste battery recycling process, the diaphragm is often directly burned as a "waste". On the one hand, the burning process does not make good use of the diaphragm resources, and on the other hand, the smoke and harmful gases produced will further pollute the environment.
[0006] Others simply utilize the diaphragm through high-temperature carbonization without truly making the most of the substances contained in the diaphragm. Summary of the invention
[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide an antibacterial non-woven fabric based on waste battery separators and a preparation method thereof.
[0008] In order to achieve the above object, the present invention is implemented through the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing an antibacterial nonwoven fabric based on waste battery separators, comprising the following steps:
[0010] Discharge the used batteries, dehydrate and dry them after discharge, then disassemble them and screen out the diaphragms;
[0011] The diaphragm is first soaked in hot water containing anionic surfactant and then in an organic solvent;
[0012] After soaking, rub the membrane in water to clean it, and then dry it to obtain a base membrane;
[0013] The base film is melted to obtain a precursor liquid, and the precursor liquid is mixed with an antibacterial agent and melt-blown to obtain an antibacterial non-woven fabric;
[0014] Or the precursor liquid is melt-blown into a non-woven fabric, and then impregnated with an antibacterial agent to obtain an antibacterial non-woven fabric.
[0015] There is no restriction on whether the diaphragm base film is PP (polypropylene) or PE (polyethylene), and there is no restriction on whether the base film is coated with a ceramic layer and a PVDF adhesive layer. By recycling the diaphragms in waste lithium-ion batteries, the recycling degree of the base material is improved while the recycling degree of the ceramic material is further improved, and the recycling value of the waste diaphragm materials is increased.
[0016] The discharge form of used batteries can be salt water discharge or charging and discharging machine discharge. The disassembly method of used batteries can be lossy disassembly or non-destructive disassembly. The lossy disassembly can use a double-axis shredder to crush and decompose the battery.
[0017] Soaking the diaphragm in hot water containing anionic surfactants can better wet the surface of the diaphragm and prepare for subsequent cleaning in water; then soaking it in an organic solution can dissolve and remove organic matter on the surface of the diaphragm, and better separate the diaphragm and inorganic matter during the subsequent rubbing and cleaning process.
[0018] In some embodiments, the discharge is performed by immersing in a salt solution, the salt solution is a Na2SO4 solution or a NaCl solution, and the mass concentration of the salt solution is 5%-10%.
[0019] Preferably, the waste batteries are immersed in a salt solution and discharged until the voltage of the batteries is less than 1.5V.
[0020] In some embodiments, in the hot water of the anionic surfactant, the mass concentration of the anionic surfactant is 10%-20%, the temperature of the hot water is 70-80° C., and the soaking time is 12-24 hours.
[0021] Preferably, the anionic surfactant is selected from carboxylates, sulfonates, sulfates or phosphates.
[0022] In some embodiments, the organic solvent is NMP, MDAc, DMF, TEP or DMSO.
[0023] Preferably, the membrane is immersed in the organic solution for 1-3 hours.
[0024] In some embodiments, the antibacterial agent is an iron ion antibacterial agent, a silver ion antibacterial agent, a zinc ion antibacterial agent, a copper ion antibacterial agent, a magnesium ion antibacterial agent, or a benzalkonium chloride antibacterial agent.
[0025] Preferably, the mass ratio of the precursor solution to the antibacterial agent is 98-99.5:0.5-2.
[0026] In some embodiments, the method further includes the steps of cleaning, demagnetizing, drying and calcining the solid precipitate obtained by rubbing and cleaning the diaphragm, so as to recover the alumina product.
[0027] The demagnetization is to pass it through a demagnetization device with a magnetic field strength of 6000±1000GS to remove magnetic substances in the solid precipitation.
[0028] Preferably, the calcination temperature is 1200-1400° C. and the calcination time is 6-8 hours.
[0029] In a second aspect, the present invention provides an antibacterial non-woven fabric based on waste battery separators, which is prepared by the preparation method.
[0030] The beneficial effects achieved by one or more embodiments of the present invention are as follows:
[0031] The cleaning agent for cleaning the waste recycling diaphragm is mainly composed of recyclable organic matter, which improves the recovery rate of the diaphragm base film while improving the reusability of the solvent and reducing costs. The separated ceramic materials are collected for screening, demagnetization and drying, and the alumina products are collected after roasting. The dissolution rate of aluminum in the prepared alumina is low (due to the high-temperature sintering and other steps, the structure of the alumina is compact).
[0032] The separated diaphragm base film is washed, dried and melted to form a precursor liquid for the antibacterial non-woven fabric.
[0033] The above scheme can recycle the diaphragms in waste or recycled lithium-ion batteries as much as possible, while reducing the pollution to the environment caused by the existing waste diaphragm treatment methods. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0035] Figure 1It is a schematic diagram of the actual production process of the diaphragm separation and recycling method for waste lithium-ion batteries. DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0037] The present invention will be further described below in conjunction with the embodiments.
[0038] Example 1
[0039] 1. Soak the used lithium-ion battery in a 10% by mass Na2SO4 solution until the battery voltage is less than 1.5V;
[0040] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0041] 3. Use a double-shaft shredder to crush the lithium battery dried in step 2, and use a wind separator to separate the diaphragm;
[0042] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, the temperature of the hot water is 75°C;
[0043] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0044] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0045] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0046] 8. The solid product 1 obtained in step 7 is calcined at 1200° C. to obtain the final product 1;
[0047] 9. Melt the base film obtained in step 8 to prepare a non-woven fabric precursor solution, mix the precursor solution with the silver ion antibacterial agent in a mass ratio of 99:1, and then melt-blown to obtain the final product 2.
[0048] Example 2
[0049] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0050] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0051] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0052] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 80°C;
[0053] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0054] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0055] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0056] 8. The solid product 1 obtained in step 7 is calcined at 1300° C. to obtain the final product 1;
[0057] 9. Melt the base film obtained in step 8 to prepare a non-woven fabric precursor solution, mix the precursor solution with the silver ion antibacterial agent in a mass ratio of 99:1, and then melt-blown to obtain the final product 2.
[0058] Example 3
[0059] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0060] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0061] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0062] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, the temperature of the hot water is 70-80°C;
[0063] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0064] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0065] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0066] 8. The solid product 1 obtained in step 7 is calcined at 1400° C. to obtain the final product 1;
[0067] 9. The base film obtained in step 8 is melted to prepare a non-woven fabric precursor solution, the precursor solution is mixed with a silver ion antibacterial agent in a mass ratio of 99:1, and then melt-blown to obtain a final product 2.
[0068] Example 4
[0069] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0070] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0071] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0072] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, the temperature of the hot water is 70-80°C;
[0073] 5. Soak the diaphragm in step 4 in an organic solution for 2 hours at room temperature;
[0074] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0075] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0076] 8. The solid product 1 obtained in step 7 is calcined at 1300° C. to obtain the final product 1;
[0077] 9. The base film obtained in step 8 is melted to prepare a non-woven fabric precursor solution, the precursor solution is mixed with the silver ion antibacterial agent in a mass ratio of 99.5:0.5, and then melt-blown to obtain the final product 2.
[0078] Example 5
[0079] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0080] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0081] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0082] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 80°C;
[0083] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0084] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0085] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0086] 8. The solid product 1 obtained in step 7 is calcined at 1300° C. to obtain the final product 1;
[0087] 9. The base film obtained in step 8 is melted to prepare a non-woven fabric precursor solution, the precursor solution is mixed with the silver ion antibacterial agent in a mass ratio of 98.5:1.5, and then melt-blown to obtain the final product 2.
[0088] Example 6
[0089] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0090] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0091] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0092] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 70°C;
[0093] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0094] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0095] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0096] 8. The solid product 1 obtained in step 7 is calcined at 1300° C. to obtain the final product 1;
[0097] 9. The base film obtained in step 8 is melted to prepare a non-woven fabric precursor solution, and the precursor solution is prepared into product 2 under the traction of hot air with a wind pressure of 80 kPa and a temperature of 200° C.;
[0098] 10. The product 2 obtained in step 9 was immersed in 40°C benzalkonium chloride solution for 30 min at a bath ratio of 1:10 (the mass ratio of textile to dye liquor in the dyeing process) and an owf of 1:0.05% (the percentage of dye relative to fabric in the dyeing and finishing process based on fabric weight, i.e. the mass ratio of dye to fabric), and then dried at 120°C hot air for 2 min to obtain the final product 2.
[0099] Example 7
[0100] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0101] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0102] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0103] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours;
[0104] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0105] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0106] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0107] 8. The solid product 1 obtained in step 7 is calcined at 1300° C. to obtain the final product 1;
[0108] 9. The base film obtained in step 8 is melted to prepare a non-woven fabric precursor solution, and the precursor solution is prepared into product 2 under the traction of hot air with a wind pressure of 80 kPa and a temperature of 200° C.;
[0109] 10. The product 2 obtained in step 9 was immersed in a 40°C benzalkonium chloride solution for 30 min at a bath ratio of 1:10 and an owf of 1:0.1%, and then dried with hot air at 120°C for 2 min to obtain the final product 2.
[0110] Example 8
[0111] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0112] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0113] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0114] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 70°C;
[0115] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0116] 6. Take the diaphragm in step 5 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0117] 7. Collect the diaphragm in step 6 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0118] 8. The solid product 1 obtained in step 7 is calcined at 1300° C. to obtain the final product 1;
[0119] 9. The base film obtained in step 8 is melted to prepare a non-woven fabric precursor solution, and the precursor solution is prepared into product 2 under the traction of hot air with a wind pressure of 80 kPa and a temperature of 200° C.;
[0120] 10. The product 2 obtained in step 9 was immersed in a 40°C benzalkonium chloride solution for 30 min at a bath ratio of 1:10 and an owf of 1:0.15%, and then dried with hot air at 120°C for 2 min to obtain the final product 2.
[0121] Example 9
[0122] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0123] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0124] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0125] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 70°C;
[0126] 5. Take the diaphragm in step 4 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0127] 6. Collect the diaphragm in step 5 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0128] 7. The solid product 1 obtained in step 6 is calcined at 1300° C. to obtain the final product 1;
[0129] 8. The base film obtained in step 6 is melted to prepare a non-woven fabric precursor solution, and the precursor solution is prepared into product 2 under the traction of hot air with a wind pressure of 80 kPa and a temperature of 200° C.;
[0130] 9. The product 2 obtained in step 8 was immersed in a 40° C. silver ion solution for 30 min at a bath ratio of 1:10 and an owf of 1:0.1%, and then dried with hot air at 120° C. for 2 min to obtain the final product 2.
[0131] Comparative Example 1
[0132] The difference from Example 1 is that the step of soaking the membrane in the organic solution in step 5 is omitted.
[0133] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0134] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0135] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0136] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 70°C;
[0137] 5. Take the diaphragm in step 4 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0138] 6. Collect the diaphragm in step 5 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0139] 7. The solid product 1 obtained in step 6 is calcined at 900° C. to obtain the final product 1;
[0140] 8. The base film obtained in step 6 is melted to prepare a non-woven fabric precursor liquid, the precursor liquid is mixed with the silver ion antibacterial agent in a mass ratio of 99:1, and then melt-blown to obtain the final product 2.
[0141] Comparative Example 2
[0142] The difference from Example 1 is that the silver ion antibacterial agent is replaced by a copper ion antibacterial agent.
[0143] 1. Soak the used lithium-ion battery in a 10% Na2SO4 solution until the battery voltage is less than 1.5V;
[0144] 2. Take the lithium-ion battery after discharge in step 1 and place it on a vibration dehydrator until it is dry;
[0145] 3. Use a double-shaft shredder to crush the lithium-ion battery dried in step 2, and use a wind separator to separate the diaphragm;
[0146] 4. Take the diaphragm separated in step 3 and soak it in a hot water solution containing 20% anionic surfactant for 24 hours, and the temperature of the hot water is 70°C;
[0147] 5. Take the diaphragm in step 4 and soak it in the organic solvent NMP for 2 hours at room temperature;
[0148] 6. Take the diaphragm in step 4 and use a rubbing cleaning device to clean it in 45°C water for 20 minutes;
[0149] 7. Collect the diaphragm in step 5 and dry it to obtain a basement membrane, and collect the precipitate in step 5 and wash and dry it to obtain a solid product 1;
[0150] 8. The solid product 1 obtained in step 6 is calcined at 1300° C. to obtain the final product 1;
[0151] 9. The base film obtained in step 6 is melted to prepare a non-woven fabric precursor liquid, the precursor liquid is mixed with a copper ion antibacterial agent in a mass ratio of 99:1, and then melt-blown to obtain the final product 2.
[0152] The dissolution conditions of the Al dissolution rate test are: 70°C, 2h, liquid-to-solid ratio 10ml / g, stirring 500rpm, normal pressure, sodium carbonate concentration 40g / L, sodium hydroxide concentration 60g / L in the dissolution solution;
[0153] The test method for the antibacterial rate of golden wine bacteria is in accordance with GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method".
[0154] It can be seen from the data in Table 1 that the recycled alumina ceramic material obtained through Examples 1-9 has good effects on Al dissolution rate and antibacterial and mildew-proof properties of non-woven fabrics.
[0155] Table 1 Al dissolution and antibacterial rate of examples and comparative examples under acidic conditions
[0156]
[0157]
[0158] The sintering temperature in Comparative Example 1 is relatively low, which makes the product structure not dense and leads to a higher dissolution rate of Al.
[0159] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an antibacterial nonwoven fabric based on waste battery separators, characterized in that: The steps include: Discharge the used batteries, dehydrate and dry them after discharge, then disassemble them and screen out the diaphragms; The diaphragm is first soaked in hot water containing anionic surfactant and then in an organic solvent; After soaking, rub the membrane in water to clean it, and then dry it to obtain a base membrane; The base film is melted to obtain a precursor liquid, and the precursor liquid is mixed with an antibacterial agent and melt-blown to obtain an antibacterial non-woven fabric; Alternatively, the precursor liquid is melt-blown into a non-woven fabric, which is then impregnated with an antibacterial agent to obtain an antibacterial non-woven fabric.
2. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: The discharge is performed by immersing in a salt solution, wherein the salt solution is a Na2SO4 solution or a NaCl solution, and the mass concentration of the salt solution is 5%-10%.
3. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: Soak the used batteries in a salt solution and discharge them until the battery voltage is less than 1.5V.
4. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: In the hot water of the anionic surfactant, the mass concentration of the anionic surfactant is 10%-20%, the temperature of the hot water is 70-80° C., and the soaking time is 12-24 hours.
5. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: The organic solvent is NMP, MDAc, DMF, TEP or DMSO.
6. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: The membrane is immersed in the organic solution for 1-3 hours.
7. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: The antibacterial agent is an iron ion antibacterial agent, a silver ion antibacterial agent, a zinc ion antibacterial agent, a copper ion antibacterial agent, a magnesium ion antibacterial agent or a benzalkonium chloride antibacterial agent; the mass ratio of the precursor solution to the antibacterial agent is 98-99.5:0.5-2.
8. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: The method also includes the steps of cleaning, demagnetizing, drying and calcining the solid precipitate obtained by rubbing and cleaning the diaphragm.
9. The method for preparing the antibacterial nonwoven fabric based on waste battery separator according to claim 1, characterized in that: The calcination temperature is 1200-1400° C., and the calcination time is 6-8 hours.
10. An antibacterial nonwoven fabric based on waste battery separator, characterized in that: Prepared by the preparation method described in any one of claims 1 to 9.